Does a selective adenosine A1 receptor agonist protect against exercise induced ischaemia in patients with coronary artery disease?. Issue 2 (1st February 2002) - Kelion, A D; Webb, T P; Gardner, M A; Ormerod, O J M; Shepherd, G L; Banning, A P
Abstract : Background: The "warm up" effect in angina may represent ischaemic preconditioning, which is mediated by adenosine A1 receptors in most models. Objective: To investigate the effect of a selective A1 agonist, GR79236 (GlaxoSmithKline), on exercise induced angina and ischaemic left ventricular dysfunction in patients with coronary artery disease. Design: A double blind crossover study. Patients: 25 patients with multivessel coronary artery disease. Interventions: On mornings one week apart, patients received intravenous GR79236 10 μg/kg or placebo, and then carried out two supine bicycle exercise tests separated by 30 minutes. Equilibrium radionuclide angiography was done before and during exercise. Results: The onset of chest pain or 1 mm ST depression was delayed and occurred at a higher rate–pressure product during the second exercise test following either placebo or GR79236. Compared with placebo, GR79236 did not affect these indices during equivalent tests. GR79236 reduced resting global ejection fraction from (mean (SD)) 63 (7)% to 61 (5)% (p < 0.05) by a selective reduction in the regional ejection fraction of "ischaemic" left ventricular sectors (those where the ejection fraction fell during the first exercise test following placebo). Ischaemic sectors showed increased function during the second test following placebo (72 (21)% v 66 (20)%; p = 0.0001), or during the first test following GR79236 (69 (21)% v 66 (20)%; p = 0.0001). Sequential exercise further increased the function of ischaemic sectors even after drug administration. Conclusions: GR79236 failed to mimic the warm up effect, and warm up occurred even in the presence of this agent. This suggests that ischaemic preconditioning is not an important component of this type of protection. The complex actions of the drug on regional left ventricular function at rest and during exercise suggest several competing A1 mediated actions.